Polymorphism of CsGaS2 – structural characterization of a new two-dimensional polymorph and study of the phase-transition kinetics12. Issue 2 (11th January 2017) - Friedrich, D.; Schlosser, M.; Weihrich, R.; Pfitzner, A.
Abstract : Anionic layers in CsGaS2 undergo a transition to infinite strands at high temperature and transfer back under pressure. Abstract : CsGaS2 - mC 64 was obtained by reaction of CsN3 with stoichiometric amounts of Ga2 S3 and S at elevated temperatures. The crystal structure of the air- and moisture stable compound was determined from single-crystal X-ray diffraction data. The colourless solid crystallizes in the monoclinic space group C 2/ c (no. 15) with the lattice parameters a = 10.5718(6) Å, b = 10.5708(6) Å, c = 16.0847(8) Å, β = 99.445(4)°, V = 1773.1(2) Å 3, and Z = 16. The compound crystallizes in the TlGaSe2 structure type and features anionic layers 2∞[Ga4 S8 4− ] consisting of corner-sharing Ga4 S10 supertetrahedra. At temperatures above 600 °C an irreversible phase-transition to CsGaS2 - mC 16 occurs. The phase-transition kinetics were studied using in situ high-temperature X-ray powder diffraction techniques. This transition can only be reversed by using high pressures (>5 GPa at 500 °C). The compound was further characterized using Raman- and diffuse reflectance spectroscopy. Chemical bonding was analysed by DFT calculations.